Implementasi Kurikulum Merdeka di SDN 38 Banyuasin Kabupaten Bayuasin - Lesi Lestiana; Yasif Arafat; Nurlina Nurlina (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to: 1) Describe the implementation of the independent curriculum at SD Negeri 38 Banyuasin, Banyuasin Regency; 2) Describe the factors that are the weaknesses and strengths of the implementation of the independent curriculum at SD Negeri 38 Banyuasin, Banyuasin Regency; 3) Describe the factors that support and inhibit the implementation of the independent curriculum at SD Negeri 38 Banyuasin. This study is a qualitative descriptive study. This study was conducted at SD Negeri 38 Banyuasin. The data collection method was carried out through observation, documentation studies and interviews. The results of this study indicate that: 1) The implementation of the independent curriculum at SD Negeri 38 Banyuasin has been carried out as it should be; 2) There are several factors that are the weaknesses and strengths of the implementation of the independent curriculum such as; (a) The lack of teacher knowledge about the implementation of the independent curriculum; (b) The low ability of teachers to use technology; (c) Limited facilities and infrastructure; (d) Limited time to adapt the independent curriculum to the previous curriculum; (e) There are challenges faced in managing the class; (f) Lack of evaluation and monitoring; (f) Resistance to ongoing changes, while the advantages are: (a) Adequate number of teachers; (b) Teachers can carry out learning activities according to students' talents and interests; (c) Teachers can choose learning methods and models according to the conditions of their students; (d) Teachers can develop their students' talents, interests and skills; (e) Teachers can encourage, motivate and increase student participation in learning activities 3) Factors that support and hinder the implementation of the independent curriculum at SD Negeri 38 Banyuasin, namely: a) The number of teachers who teach is sufficient; d) Support from the Banyuasin Regency Education Office; c) Availability of infrastructure that supports the implementation of the independent curriculum; d) Support from parents/guardians e) Collaboration between schools. While the inhibiting factors are: 1) Limited human resources (teachers). 2) Limited facilities and infrastructure; 3) Limited study time and the overwhelming administrative workload of teachers; 4) Lack of optimal involvement of parents and the community; 5) Limited operational funds